2003
DOI: 10.1046/j.1474-919x.2003.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of a novel song and an increase in repertoire size in an island population of an Australian songbird

Abstract: Cultural innovations are commonly noted in animals, but times of development of novel traits are usually unknown. We report here a novel song type arising in a bird population on an offshore island of Western Australia where the time of colonization of the island by the Western Gerygone Gerygone fusca is known. On the mainland, a single song type is widespread. On Rottnest Island, many individuals sing a different type of song and a number possess a repertoire of two song types: the standard song shared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
3
31
0
1
Order By: Relevance
“…Like in Azorean Goldcrests, directional patterns of dialect distribution also revealed the colonization history of Whitecrowned Sparrows, Zonotrichia leucophrys, on islands of the San Francisco Bay (Slabbekoorn et al 2003). In the Western Gerygone, Gerygone fuscata, on Australian offshore islands, newly developed island dialect songs had been fixed in the population even during a colonization phase of 50 years only (Baker 2003). Finally, in small isolated populations absence or rarity of conspecific tutors might lead to an accumulation of alien imitations in passerine songs as was reported from sedentary Nearctic and Neotropical Sedge Wrens, Cistiphora platensis (Kroodsma et al 1999).…”
Section: Phylogeny and Systematicsmentioning
confidence: 93%
“…Like in Azorean Goldcrests, directional patterns of dialect distribution also revealed the colonization history of Whitecrowned Sparrows, Zonotrichia leucophrys, on islands of the San Francisco Bay (Slabbekoorn et al 2003). In the Western Gerygone, Gerygone fuscata, on Australian offshore islands, newly developed island dialect songs had been fixed in the population even during a colonization phase of 50 years only (Baker 2003). Finally, in small isolated populations absence or rarity of conspecific tutors might lead to an accumulation of alien imitations in passerine songs as was reported from sedentary Nearctic and Neotropical Sedge Wrens, Cistiphora platensis (Kroodsma et al 1999).…”
Section: Phylogeny and Systematicsmentioning
confidence: 93%
“…A tendency to maximise variability within a system may appear in the form of deliberate innovations observed both in humans (Labov, 2011) and birds (Baker et al, 2003;Slater & Lachlan, 2003). Ford (1991) suggested that innovation must play a major role in the formation of new call types in killer whale dialects, while random errors can only alter the structure of existing types.…”
Section: Proximate Mechanisms Of Dialect Changementioning
confidence: 99%
“…One example is song evolution, for which inconsistent findings have often been reported when comparing island and mainland populations. Vocalizations may be subject to direct selection as a consequence of island isolation (Baker and Jenkins 1987, Baker et al 2003, 2006, Päckert and Martens 2004), however they may also change as a consequence of indirect selection on morphological attributes that influence sound production. For instance, islands tend to promote larger body sizes (the ‘island rule’), both in structure and mass in small mammals (Van Valen 1973, Lomolino 2005, Lomolino et al 2012) and birds (Clegg and Owens 2002, Scott et al 2003).…”
mentioning
confidence: 99%